Gas Displacement Engineering Test by Combination of Low and Medium Pressure Injection with Liquid CO2 in High Gas and Low Permeability Coal Seam - Hu Wen; Mingyang Liu; Gaoming Wei; Xiaowei Zhai; Shixing Fan; Xiaojiao Cheng; Hu Wang; Jianchi Hao (Geofluids)
Mining high-gas coal seams in China has the characteristics mining of deep, high storage and low permeability, and low drainage efficiency, which seriously restrict the efficient prevention and control of mine gas disasters. Based on the characteristics of low viscosity and permeability, phase change pressurization, and strong adsorption potential energy of liquid CO2, the technology system of liquid CO2 displacement for high-gas and low-permeability coal seam was developed, and field industrial of low-pressure (0.5~2.5 MPa) and medium-pressure (2.5~15.0 MPa) combined injection test was carried out. In this test, the mode of injection followed by drainage was adopted, and the gas drainage effect was investigated for 30 days. The test results show that the effective influence radius of CO2 in this test is 20 m, and the liquid seepage radius is 5 to 7 m. After the injection of liquid CO2 into coal seam, the average gas drainage concentration and drainage purity of all drainage holes were increased by 3.2 and 3.4 times, respectively, and the gas promotion effect was significant. Taking the liquid CO2 low-medium-pressure displacement gas test area as the calculation unit, from the comprehensive benefit analysis, compared with the original drainage mode, the liquid CO2-combined pressure injection process can save 34.7% of the engineering cost and shorten the gas drainage standard time by 45.9%. Therefore, the application of this technology has important technical support and reference significance for the efficient management of gas in the same type of mine.